Elasticity reducing agent for early-strength impervious sprayed concrete in water-rich area as well as preparation method and application of elasticity reducing agent

By using nanocomposite early strength and viscosity-enhancing materials and other components in water-rich regional tunnel projects, the cohesion and hydration rate of sprayed concrete are improved, and the problems of large rebound rate, poor density and insufficient water permeability of sprayed concrete are solved, achieving the effects of early strength, low rebound and high density.

CN120192113AActive Publication Date: 2025-06-24HUBEI COMM INVESTMENT TRANSPORTATION PLANNING & DESIGN RES CO LTD +2
View PDF 4 Cites 0 Cited by

Patent Information

Application Number
CN202510334348.2
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2025-03-20
Publication Date
2025-06-24
Estimated Expiration
2045-03-20

AI Technical Summary

Technical Problem

In water-rich regional tunnel projects, the sprayed concrete has a large rebound rate, poor density, and insufficient water permeability, which affects support safety.

Method used

An elastic reducing agent for sprayed concrete in water-rich areas is adopted. The elastic reducing agent includes nanocomposite early strength and tackifying materials, pro-setting components, adjusting components and filling materials. By increasing the cohesion and hydration rate of sprayed concrete, the density and early strength are improved, and the rebound rate is reduced.

Benefits of technology

It effectively reduces the rebound rate of sprayed concrete, improves the strength and density of young age, realizes the early strength, low rebound and high density of sprayed concrete, and solves the problem of water seepage in sprayed concrete in water-rich areas.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure SMS_1
    Figure SMS_1
  • Figure SMS_2
    Figure SMS_2
Patent Text Reader

Abstract

The invention discloses an elasticity reducing agent for early-strength impervious sprayed concrete in a water-rich area. The elasticity reducing agent comprises a tackifying and early-strength component, a coagulating component, an adjusting component and a filling material, wherein the tackifying early-strength component is a nano composite early-strength tackifying material, and the mass ratio of the tackifying early-strength component to the nano composite early-strength tackifying material is 40-60%; the coagulation accelerating component is composed of one or more of triisopropanolamine, calcium formate, sodium sulfate and lithium sulfate, and the mass ratio of the coagulation accelerating component to the lithium sulfate is 30-50%; the adjusting component is composed of one or more of a powder water reducing agent, boric acid, sodium gluconate, sodium tripolyphosphate and citric acid, the mass ratio is 1-5%, and the balance is a filling material. The invention further discloses a preparation method and application of the elasticity reducing agent for the early-strength anti-seepage sprayed concrete in the water-rich area. The method can improve the strength of the sprayed concrete at the juvenile stage, reduce the springback amount of the sprayed concrete and improve the compactness and strength of the concrete.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to the technical field of building material concrete admixtures, and more specifically, to a resilient reducing agent for early-strength anti-seepage shotcrete in water-rich areas, and a preparation method and application thereof. Background Art

[0002] Shotcrete refers to a special type of concrete that uses a spraying machine and compressed air to spray concrete onto the sprayed surface at high speed, quickly solidify and generate strength. Compared with cast-in-place concrete, machine spraying construction has the advantages of short solidification time, convenient construction, shortened construction period, and cost savings. It is widely used in spray reinforcement of coal mine shafts, tunnels, culverts and other projects. However, when shotcrete is used in tunnel projects in water-rich areas, due to the high humidity and visible water on the tunnel rock wall, the bonding force between the shotcrete and the wall becomes smaller, resulting in a large rebound rate. At the same time, the poor cohesion of the concrete leads to poor density after spraying, resulting in poor water permeability resistance of the shotcrete. Large-scale penetration often occurs after the spraying is completed, affecting the support safety.

[0003] Adding thickening materials to concrete can improve the cohesion of concrete, thereby reducing the rebound rate. There are two types of existing thickeners: inorganic and organic. Inorganic thickeners have no significant improvement on the bonding viscosity between particles and aggregates; organic thickeners will cause the pores to become larger and form harmful pores after water evaporation or hydration, resulting in a decrease in concrete strength. Both types of thickeners have their own defects. Furthermore, in water-rich areas, due to the presence of clear water on the surface of the rock formation, the initial bonding force will slowly weaken and produce blocks under the continuous infiltration of water. Water will continue to penetrate into the incompletely hydrated concrete, forming water channels, affecting the durability of the concrete. Simply increasing the bonding force with the rock formation cannot significantly improve the rebound and durability of the shotcrete. It is necessary to improve the strength of the shotcrete in its early stage on the basis of thickening, shorten the early strength development time, and weaken the influence of external water on the hydration process, so as to effectively improve the bonding force and density of the concrete. However, after the addition of traditional early strength agents, it often affects the working performance of the concrete before spraying, seriously affecting the construction safety and quality. Summary of the invention

[0004] An object of the present invention is to provide a rebound reducing agent for early-strength and impermeable shotcrete in water-rich areas, a preparation method and an application thereof. The rebound reducing agent is a rebound reducing agent that can improve the strength of shotcrete in the early age, reduce the rebound amount of shotcrete, improve the compactness and strength of concrete, and does not affect the slump retention performance of concrete; the cohesion and hydration rate of shotcrete are improved through the early-strength and viscosity-increasing components, the paste wrapping property of concrete, the adhesion and wall hanging after spraying, and the rapid hardening performance are improved, thereby reducing the rebound rate and increasing the thickness of the first spraying; at the same time, the nano-particles containing aluminum ions loaded on the hydrogel rapidly hydrate in the pores, and the harmful pores are filled by the directional hydration with the nucleation effect of graphene, effectively improving the compactness and early strength of the shotcrete material, so as to achieve the early strength, low rebound and high compactness of the shotcrete, and solve the problems of large rebound amount and serious water seepage of shotcrete in water-rich areas.

[0005] In order to solve the above technical problems, the present invention provides a rebound reducing agent for early-strength and impermeable shotcrete in water-rich areas, which includes a viscosity-increasing and early-strength component, a coagulation accelerating component, a regulating component and a filling material; wherein, the viscosity-increasing and early-strength component is a nano-composite early-strength and viscosity-increasing material, and the mass ratio is 40-60%; the coagulation accelerating component is composed of one or more of triisopropanolamine, calcium formate, sodium sulfate, lithium sulfate, and the mass ratio is 30-50%; the regulating component is composed of one or more of a powder water reducing agent, boric acid, sodium gluconate, sodium tripolyphosphate, citric acid, and the mass ratio is 1-5%, and the rest is a filling material.

[0006] Preferably, the nano-composite early-strength and viscosity-increasing material is prepared by modifying cationic polyacrylamide with a hydrogel and then adsorbing C-A-S-H nano-crystallization nuclei. The preparation method includes the following steps: S1. Mix the monomers AMPS, i.e., 2-acrylamido-2-methylpropanesulfonic acid, and DMAA, i.e., N,N-dimethylacrylamide, in a mass ratio of 1:1-1:5, totaling 100 parts, and prepare P(AMPS-co-DMAA) hydrogel by copolymerization; at the same time, during the mixing process, 100 parts of a cationic polyacrylamide aqueous solution with a concentration of 0.01-0.05% is added dropwise to the copolymerization solution to obtain a modified amide intermediate. S2. Slowly drip 50 mL of sodium silicate solution and 50 mL of a mixed solution of calcium nitrate and aluminum nitrate into 100 mL of a PCE, i.e., polycarboxylate superplasticizer, aqueous solution at a dropping rate of 2.0 mL / min at the same time. During the dropping period, the pH value of the system is monitored in real time, and the pH value of the system is adjusted to 12 with NaOH solution and nitric acid solution; after all the reactants are dropped, the reactants are continuously stirred at 30-35°C for 24 h to obtain a milky white C-A-S-H nano-crystallization nucleus suspension. S3. Filter the prepared modified amide intermediate and dry it at 50 - 60°C for 2 days. After drying, soak it in a C - A - S - H nanocrystal nucleus solution with a concentration of 10 - 25%. After fully soaking for 10 - 12 hours, filter to obtain a saturated hydrogel, dry it at 50 - 60°C for 2 days. After drying, add 5 - 10 g of graphene powder, mix, and then pulverize to prepare a nano - composite early - strength and viscosity - increasing material.

[0007] Preferably, the modulus of sodium silicate is 2.2 - 2.6; in the mixed solution of calcium nitrate and aluminum nitrate, the mass concentration of calcium nitrate is 10 - 15%, and the mass concentration of aluminum nitrate is 20 - 30%; PCE is a polycarboxylate water - reducing agent with a mass concentration of 5 - 10%.

[0008] Preferably, the molecular weight of the cationic polyacrylamide is 600,000 - 1,000,000.

[0009] Preferably, the graphene is industrial - grade graphene with a density of 10 - 50 g / cm3.

[0010] Preferably, the filling material is composed of one or several of stone powder, silica fume, and tailings powder.

[0011] The present invention also provides a preparation method of a rebound - reducing agent for early - strength and impermeable shotcrete in water - rich areas. Mix the viscosity - increasing and early - strength component, setting - accelerating component, regulating component, and filling material according to the designed mass ratio to obtain a rebound - reducing agent for early - strength and impermeable shotcrete in water - rich areas.

[0012] Preferably, use a hydrogel - modified cationic polyacrylamide, and then adsorb C - A - S - H nanocrystal nuclei to prepare a nano - composite early - strength and viscosity - increasing material as the viscosity - increasing and early - strength component.

[0013] The present invention also provides an application of a rebound - reducing agent for early - strength and impermeable shotcrete in water - rich areas. Add the rebound - reducing agent to the shotcrete in an internal - admixture manner, that is, replacing cement. The dosage of the rebound - reducing agent is 1 - 3% of the mass of the cementitious material in the shotcrete.

[0014] The present invention has at least the following beneficial effects: The present invention provides a rebound - reducing agent that can improve the strength of shotcrete in the early age, reduce the rebound amount of shotcrete, and improve the density and strength of concrete. It aims to enhance the cohesiveness and hydration rate of shotcrete through the viscosity - increasing and early - strength component, improve the paste - wrapping property of concrete, the adhesion and wall - hanging after spraying, and the rapid - hardening performance, thereby reducing the rebound rate and increasing the thickness of a single - shot spraying; through the rapid hydration of aluminum - ion - containing nanoparticles loaded on the hydrogel, directionally filling harmful pores, effectively improving the density and early strength of shotcrete, and achieving early - strength, low - rebound, and high - density of shotcrete.

[0015] ① The rebound reducer aims at the characteristics of shotcrete in water-rich areas (poor adhesion to rock formations, low early strength and easy falling off, and poor water seepage resistance). It improves the construction quality of shotcrete from three aspects: collapse prevention before shotcreting, viscosity enhancement and early strength after shotcreting, and later compaction and anti-seepage. The rebound rate in water-rich areas is less than 6%, the 1h compressive strength is increased by 500%, and the penetration height ratio is less than 10%.

[0016] ② The CASH nanocrystalline core in the elasticity reducing agent is wrapped by hydrogel and is slowly released during mixing and transportation, which does not affect the collapse resistance of concrete before spraying. When the accelerator is added, a large amount of needle-shaped ettringite is generated, which destroys the surface structure of the hydrogel. The CASH nanocrystalline core is quickly dissolved and released. The CASH nanocrystalline core provides nucleation sites, and the aluminum gel promotes rapid hydration, quickly fills the gaps in the ettringite, forms a dense structure, and produces early strength.

[0017] ③The elasticity reducing agent adopts low molecular weight cationic polyacrylamide. Cationic polyacrylamide is a linear polymer compound. Its low molecular weight can effectively reduce the pores formed by water adsorption and aggregation. The nanocrystalline core and graphene will simultaneously induce cement hydration to form a large amount of gel to fill the structural pores during the evaporation of water around the polymer chain, thereby achieving directional filling of harmful pores and improving the density and strength of the hydration product.

[0018] Other advantages, objectives and features of the present invention will be embodied in part through the following description, and in part will be understood by those skilled in the art through study and practice of the present invention. DETAILED DESCRIPTION

[0019] In order to better understand the purpose, structure and function of the present invention, the present invention is further described in detail below in conjunction with embodiments so that those skilled in the art can implement it according to the description.

[0020] It should be noted that the experimental methods described in the following embodiments are conventional methods unless otherwise specified, and the reagents and materials can be obtained from commercial channels unless otherwise specified.

[0021] Component materials not otherwise specified in this application are all commercially available products.

[0022] The 2-acrylamido-2-methylpropanesulfonate, N,N-dimethylacrylamide and cationic polyacrylamide are commercially available products; The triisopropanolamine, calcium formate, sodium sulfate and lithium sulfate are all commercially available products; The powder water reducer, boric acid, sodium gluconate, sodium tripolyphosphate and citric acid are commercially available products; The filling material is composed of one or more of stone powder, silica ash and tailings powder, all of which are commercially available products.

[0023] The elastic modulus reducing agent of the present invention is composed of a viscosity-increasing and early-strengthening component, a coagulation-promoting component, and a regulating component, and the dosage is 1-3% of the mass of the cementitious material in the shotcrete. Among them, the viscosity-increasing and early-strengthening component is a nano-composite early-strengthening and viscosity-increasing material, with a mass ratio of 40-60%; the coagulation-promoting component is composed of one or several of triisopropanolamine, calcium formate, sodium sulfate, and lithium sulfate, with a mass ratio of 30-50%; the regulating component is composed of one or several of a powder water reducer, boric acid, sodium gluconate, sodium tripolyphosphate, and citric acid, with a mass ratio of 1-5%, and the rest is a filling material, and the filling material is composed of one or several of stone powder, silica fume, and tailings powder.

[0024] The nano-composite early-strengthening and viscosity-increasing material is a multifunctional viscosity-increasing material with early strength, slow release, and ability to directionally fill pores. It is prepared by modifying cationic polyacrylamide with hydrogel and then adsorbing C-A-S-H nanocrystallization nuclei. The modified polyacrylamide has a good viscosity-increasing effect in concrete. The C-A-S-H nanoparticles in the hydrogel will move along with the polyacrylamide molecules. During the hydration process, they are released into the liquid phase around the polymer chains. The nanoparticles provide crystallization nuclei, and the highly active aluminum ions promote rapid hydration. Nucleation occurs rapidly where the polyacrylamide molecules enclose water, promoting the formation of hydration products. It acts synergistically with graphene to fill the pores after water hydration and evaporation, preventing the formation of harmful pores locally. At the same time, it acts synergistically with the accelerating agent to enable the rapid hydration of concrete. Its preparation process is as follows: S1. Mix the monomers AMPS (2-acrylamido-2-methylpropanesulfonic acid) and DMAA (N,N-dimethylacrylamide) in a mass ratio of 1:1-1:5, totaling 100 parts, and prepare P(AMPS-co-DMAA) hydrogel by copolymerization. At the same time, during the mixing process, 100 parts of a cationic polyacrylamide aqueous solution with a concentration of 0.01-0.05% is added dropwise to the copolymerization solution to obtain a modified amide intermediate. The cationic polyacrylamide has a low molecular weight, with a molecular weight of 600,000-1,000,000. Too low a molecular weight has a poor viscosity-increasing effect, and too high a molecular weight will cause excessive entanglement and wrapping of cement particles, reducing the strength of concrete.

[0025] S2. Slowly and simultaneously drip 50 mL of sodium silicate solution and 50 mL of the mixed solution of calcium nitrate and aluminum nitrate into 100 mL of PCE aqueous solution at a dropping rate of 2.0 mL / min. During the dropping process, the pH value of the system is monitored in real time with a high-precision pH meter, and at the same time, the pH value of the system is adjusted to about 12 with NaOH solution and nitric acid solution. After all the reactants are dropped, the reactants are continuously stirred at 30 - 35 °C for 24 h to obtain a milky white C-A-S-H nanocrystal nucleus suspension with a relatively high active aluminum content. The modulus of sodium silicate is between 2.2 and 2.6, the mass concentration of calcium nitrate in the mixed solution of calcium nitrate and aluminum nitrate is 10 - 15%, the mass concentration of aluminum nitrate is 20 - 30%, PCE is a polycarboxylate water reducer, and the mass concentration is 5 - 10%.

[0026] S3. Filter the prepared modified amide intermediate and dry it at 50 - 60 °C for 2 days. After drying, soak it in a C-A-S-H nanocrystal nucleus solution with a concentration of 10 - 25%. After fully soaking for 10 - 12 h, filter to obtain a saturated hydrogel, dry it at 50 - 60 °C for 2 days. After drying, add 5 - 10 g of graphene powder, mix and then crush to prepare a nano-composite early strength and viscosity-increasing material. The graphene is industrial-grade graphene with a density of 10 - 50 g / cm3. After the saturated hydrogel is dried, it is easy to produce cementation during the crushing process. After mixing and wrapping with graphene, it can better separate the crushed fragments and powders, playing a dispersing role. During the hydration process, the graphene provides crystal nuclei, which will further promote the hydration of cement particles around the viscosity-increasing agent, fill the pores, and improve the impermeability and compressive strength of shotcrete.

[0027] Example 1 A rebound reducer for early strength and impermeable shotcrete in water-rich areas provided in this example includes the following components by mass: 40 parts of viscosity-increasing and early strength component, 50 parts of coagulation promoting component, 5 parts of regulating component, and 5 parts of filling material.

[0028] Among them, the coagulation promoting component includes 20 parts of triisopropanolamine and 30 parts of lithium sulfate; The regulating component includes 2 parts of powder water reducer, 1 part of boric acid, and 2 parts of sodium gluconate; The filling material includes 5 parts of tailings powder.

[0029] The viscosity-increasing and early strength component of this example is a nano-composite early strength and viscosity-increasing material, and its preparation method is as follows: S1. Mix monomer AMPS (2-acrylamido-2-methylpropanesulfonic acid) and DMAA (N,N-dimethylacrylamide) in a mass ratio of 1:1, totaling 100 parts, and prepare P(AMPS-co-DMAA) hydrogel by copolymerization. Meanwhile, during the mixing process, add 100 parts of 0.05% cationic polyacrylamide aqueous solution dropwise into the blending solution to obtain a modified amide intermediate. The cationic polyacrylamide has a low molecular weight, with a molecular weight of 600,000 - 1,000,000.

[0030] S2. Slowly drip 50 mL of sodium silicate solution and 50 mL of a mixed solution of calcium nitrate and aluminum nitrate into 100 mL of PCE aqueous solution simultaneously at a dropping rate of 2.0 mL / min. During the dropping process, monitor the pH value of the system in real time with a high-precision pH meter, and adjust the pH value of the system to about 12 with NaOH solution and nitric acid solution. After all the reactants are dropped, continue to stir the reactants in a 35°C environment for 24 h to obtain a milky white C-A-S-H nanocrystal nucleus suspension with a high active aluminum content. The modulus of sodium silicate is between 2.2 - 2.6, the mass concentration of calcium nitrate in the mixed solution of calcium nitrate and aluminum nitrate is 15%, the mass concentration of aluminum nitrate is 30%, and PCE is a polycarboxylate superplasticizer with a mass concentration of 10%.

[0031] S3. Filter the prepared modified amide intermediate and dry it at 60°C for 2 days. After drying, soak it in a 25% C-A-S-H nanocrystal nucleus solution. After fully soaking for 12 h, filter to obtain a saturated hydrogel, dry it at 60°C for 2 days, add 10 g of graphene powder after drying, mix, and then pulverize to prepare a nano-composite early strength and viscosity-increasing material.

[0032] A preparation method of a rebound reducer for early strength and anti-seepage shotcrete in water-rich areas. Mix the following components by mass: 40 parts of viscosity-increasing and early strength component, 50 parts of coagulation promoting component, 5 parts of regulating component, and 5 parts of filling material.

[0033] Add the rebound reducer prepared in Example 1 to the shotcrete by internal admixture, that is, replacing cement. The dosage of the rebound reducer is 2% of the mass of the cementitious material in the shotcrete.

[0034] Example 2 A rebound reducer for early strength and anti-seepage shotcrete in water-rich areas provided in this example includes the following components by mass: 50 parts of viscosity-increasing and early strength component, 40 parts of coagulation promoting component, 3 parts of regulating component, and 7 parts of filling material.

[0035] Among them, the coagulation promoting component includes 20 parts of triisopropanolamine and 20 parts of lithium sulfate; The regulating component includes 1 part of powder superplasticizer, 1 part of boric acid, and 1 part of sodium gluconate; The filling material includes 7 parts of tailings powder.

[0036] The rest are exactly the same as those in Example 1.

[0037] Example 3 A rebound reducing agent for early-strength and impermeable shotcrete in water-rich areas provided in this example includes the following components by mass: 60 parts of thickening and early-strengthening component, 30 parts of coagulation promoting component, 1 part of regulating component, and 9 parts of filling material.

[0038] Among them, the coagulation promoting component includes 10 parts of triisopropanolamine and 20 parts of lithium sulfate; The regulating component includes 0.4 part of powder water reducing agent, 0.2 part of boric acid, and 0.4 part of sodium gluconate; The filling material includes 9 parts of tailings powder.

[0039] The rest are exactly the same as those in Example 1.

[0040] Comparative Example 1 It is a reference C25 shotcrete without adding a rebound reducing agent.

[0041] Comparative Example 2 According to the formulation ratio of Example 3, the hydrogel and the nano C-A-S-H crystal nucleus early-strengthening agent are not pre-adsorbed and are directly added separately. The rest are the same as those in Example 3.

[0042] The thickening and early-strengthening component in this example is a nano-composite early-strengthening and thickening material, and its preparation method is as follows: S1. Mix the monomers AMPS (2-acrylamido-2-methylpropanesulfonic acid) and DMAA (N,N-dimethylacrylamide) in a mass ratio of 1:1, totaling 100 parts, and prepare P(AMPS-co-DMAA) hydrogel by copolymerization method.

[0043] S2. Slowly drip 50 mL of sodium silicate solution and 50 mL of mixed solution of calcium nitrate and aluminum nitrate into 100 mL of PCE aqueous solution at a dropping rate of 2.0 mL / min simultaneously. During the dropping period, the pH value of the system is monitored in real time with a high-precision pH meter, and the pH value of the system is adjusted to about 12 with NaOH solution and nitric acid solution. After all the reactants are dropped, the reactants are continuously stirred in an environment of 35 °C for 24 h to obtain a milky white C-A-S-H nano-crystal nucleus suspension with a relatively high active aluminum content. The modulus of the sodium silicate is between 2.2 and 2.6, the mass concentration of calcium nitrate in the mixed solution of calcium nitrate and aluminum nitrate is 15%, the mass concentration of aluminum nitrate is 30% respectively, and PCE is a polycarboxylate water reducing agent with a mass concentration of 10%.

[0044] S3. Mix the P(AMPS-co-DMAA) hydrogel and the C-A-S-H nanocrystal nucleus suspension to prepare a nano-composite early-strength and viscosity-increasing material.

[0045] Comparative Example 3 According to the formulation ratio of Example 3, without adding graphene, the dried hydrogel is directly crushed and then a resilience-reducing agent is added. The rest is the same as in Example 3.

[0046] The viscosity-increasing and early-strength component of this example is a nano-composite early-strength and viscosity-increasing material, and its preparation method is as follows: S1. Mix the monomers AMPS (2-acrylamido-2-methylpropanesulfonic acid) and DMAA (N,N-dimethylacrylamide) in a mass ratio of 1:1, totaling 100 parts, and prepare the P(AMPS-co-DMAA) hydrogel by copolymerization. At the same time, during the mixing process, 100 parts of a 0.05% concentration cationic polyacrylamide aqueous solution is added dropwise to the copolymerization solution to obtain a modified amide intermediate. The cationic polyacrylamide has a low molecular weight, with a molecular weight of 600,000 - 1,000,000.

[0047] S2. Slowly drip 50 mL of sodium silicate solution and 50 mL of a mixed solution of calcium nitrate and aluminum nitrate into 100 mL of PCE aqueous solution at a drip rate of 2.0 mL / min simultaneously. During the dripping process, the pH value of the system is monitored in real time with a high-precision pH meter, and at the same time, the pH value of the system is adjusted to about 12 with NaOH solution and nitric acid solution. After all the reactants are added dropwise, the reactants are continuously stirred at 35°C for 24 h to obtain a milky white C-A-S-H nanocrystal nucleus suspension with a high active aluminum content. The modulus of the sodium silicate is between 2.2 - 2.6, the mass concentration of calcium nitrate in the mixed solution of calcium nitrate and aluminum nitrate is 15%, the mass concentration of aluminum nitrate is 30% respectively, and PCE is a polycarboxylate superplasticizer with a mass concentration of 10%.

[0048] S3. Filter the obtained modified amide intermediate and dry it at 60°C for 2 days. After drying, soak it in a 25% concentration C-A-S-H nanocrystal nucleus solution. After soaking for 12 h, filter to obtain a saturated hydrogel, and dry it at 60°C for 2 days to prepare a nano-composite early-strength and viscosity-increasing material.

[0049] Comparative Example 4 Add the resilience-reducing agent prepared in Example 3 to the shotcrete in an internal admixture method, that is, replacing cement, and the dosage of the resilience-reducing agent is 4% of the mass of the cementitious materials in the shotcrete.

[0050] The rest is exactly the same as in Example 3.

[0051] Comparative Example 5 A rebound reducing agent for early-strength and impermeable shotcrete in water-rich areas provided by this embodiment includes the following components by mass: 70 parts of thickening and early-strength component, 24 parts of coagulation promoting component, 1 part of regulating component, and 5 parts of filling material.

[0052] Among them, the coagulation promoting component includes 10 parts of triisopropanolamine and 14 parts of lithium sulfate; The regulating component includes 0.4 part of powder water reducer, 0.2 part of boric acid, and 0.4 part of sodium gluconate; The filling material includes 5 parts of tailings powder.

[0053] The rest are exactly the same as those in Example 3.

[0054] Comparative Example 6 HT-01 rebound reducing agent product of Wuhan Yuanjin Building Materials Technology Co., Ltd.

[0055] Prepare shotcrete for the above-mentioned examples and comparative examples according to Table 1 below.

[0056] Table 1 Mix proportion of C25 shotcrete (kg / m³) Conduct various performance tests on the above-mentioned examples and comparative examples as shown in Table 2 below.

[0057] Table 2 Performance test As can be seen from the test results in Table 2, for the elastic modulus reducing agents with different components used in Examples 1, 2, and 3, by comparing with Comparative Example 1, it can be known that the use of the elastic modulus reducing agent can effectively increase the plastic viscosity and 1-hour strength of shotcrete, thereby improving the adhesion during shotcrete spraying and the early strength of the concrete, reducing the rebound rate, making the concrete more dense, increasing the 28-day compressive strength and bond strength, and reducing the anti-seepage height ratio; by comparing the test results of Examples 1, 2, 3, and 5, it can be seen that as the viscosity-increasing and early-strengthening component increases, the viscosity of the shotcrete further increases, the rebound rate further decreases, and the strength at each age also increases. After the dosage exceeds 60%, the improvement effect weakens, and the 28-day strength decreases slightly; by comparing the test results of Example 3 and Comparative Example 2, when the hydrogel and the nano C-A-S-H crystal nucleus early-strengthening agent are not pre-adsorbed, the nano C-A-S-H crystal nucleus early-strengthening agent will significantly affect the slump retention performance of the concrete, and it no longer has workability during spraying and cannot be tested subsequently; by comparing Example 3 and Comparative Example 3, after the dried hydrogel is directly crushed without adding graphene coating, the powders are prone to agglomeration with each other and are not easily dispersed in the concrete, resulting in uneven concrete quality, increased porosity, and reduced strength and anti-seepage performance. By comparing Example 3 and Comparative Example 4, after the dosage of the elastic modulus reducing agent is increased, the time-dependent loss of the concrete becomes larger, the rebound amount increases, and the anti-seepage height ratio also increases. By comparing Example 3 and Comparative Example 6, the dosage of the product in this application is lower than that of the elastic modulus reducing agent products on the market, and the spraying effect and the strength of the concrete at each age are higher than those of the comparative products.

[0058] This product has been successfully applied in Tianchiya Tunnel on the Shiyan-Wufeng South Expressway. Tianchiya Tunnel passes through a water-rich fractured zone. The seepage volume of the rock mass in some sections reaches 100 L / min, the seepage pressure is high, the rock surface is wet and slippery, the interface is soft, the adhesion of the concrete is poor, the rebound rate of traditional wet shotcrete reaches 50%, there are a large number of honeycomb-like voids in the primary support structure, and the 28-day compressive strength is only 20 MPa, which cannot meet the support requirements. After using the product of the present invention, the initial setting time is shortened to 3 minutes, meeting the requirement of rapid setting in a dynamic water environment, the rebound rate is reduced to 7.5%, the 28-day compressive strength is increased to 40.5 MPa, the bond strength reaches 2.2 MPa, the density of the sprayed body reaches 95%, and the number of seepage points is reduced by 83%. This product has successfully solved the technical bottlenecks such as poor adhesion of shotcrete in water-rich strata and weak anti-seepage of the support body, and formed a zero-leakage shotcrete structure in water-rich tunnels.

[0059] According to the above test results, the present invention has successfully formulated a rebound reducer that can reduce the rebound rate of shotcrete in water-rich areas, improve the strength of shotcrete in the early age, and enhance the density and strength of concrete by the synergistic action of tackifying and early-strengthening components, coagulation-promoting components, and regulating components. The tackifying and early-strengthening components enhance the cohesiveness and hydration rate of shotcrete, improve the paste wrapping property of concrete, the adhesion and wall-hanging after spraying, and the rapid hardening performance, thereby reducing the rebound rate and increasing the thickness of a single shot. The nano-particles containing aluminum ions loaded on the hydrogel rapidly hydrate in the pores, directionally filling harmful pores, effectively improving the density and early strength of shotcrete, and achieving early strength, low rebound, and high density of shotcrete.

[0060] It can be understood that the present invention is described through some embodiments. As is known to those skilled in the art, various changes or equivalent replacements can be made to these features and embodiments without departing from the spirit and scope of the present invention. Although the embodiments of the present invention have been disclosed as above, they are not limited to only the applications listed in the specification and embodiments. It can be fully applied to various fields suitable for the present invention. For those familiar with the field, additional modifications can be easily achieved. Therefore, without departing from the general concept defined by the claims and the equivalent scope, the present invention is not limited to specific details and the embodiments shown and described herein.

Claims

1. A resilient agent for early-strength and anti-seepage shotcrete in water-rich areas, characterized in that: It includes a thickening and early strength component, a coagulant component, an adjusting component and a filling material; among them, the thickening and early strength component is a nano-composite early strength thickening material, accounting for 40-60% by mass; the coagulant component is composed of one or more of triisopropanolamine, calcium formate, sodium sulfate and lithium sulfate, accounting for 30-50% by mass; the adjusting component is composed of one or more of powder water reducer, boric acid, sodium gluconate, sodium tripolyphosphate and citric acid, accounting for 1-5% by mass, and the rest are filling materials.

2. The elasticity reducing agent for early-strength anti-seepage shotcrete in water-rich areas according to claim 1, characterized in that: The nano-composite early strength and viscosity-enhancing material is prepared by hydrogel-modified cationic polyacrylamide and then adsorbing CASH nano-crystal cores. The preparation method comprises the following steps: S1. Mixing monomers AMPS (2-acrylamido-2-methylpropanesulfonic acid) and DMAA (N,N-dimethylacrylamide) in a mass ratio of 1:1-1:5, a total of 100 parts, and preparing P (AMPS-co-DMAA) hydrogel by a co-polymerization method; while adding 100 parts of a 0.01-0.05% concentration cationic polyacrylamide aqueous solution to the co-polymerized solution by dropwise addition during the mixing process, to obtain a modified amide intermediate; S2, 50 mL of sodium silicate solution and 50 mL of mixed solution of calcium nitrate and aluminum nitrate were slowly dripped into 100 mL of PCE (polycarboxylate water-reducing agent) aqueous solution at a dripping rate of 2.0 mL / min, and the pH value of the system was monitored in real time during the dripping, and the pH value of the system was adjusted to 12 with NaOH solution and nitric acid solution; after all the reactants were dripped, the reactants were stirred for 24 h at 30-35°C to obtain a milky white CASH nanocrystal core suspension; S3. Filter the prepared modified amide intermediate and dry it at 50-60°C for 2 days. After drying, soak it in a 10-25% concentration of CASH nanocrystal core solution. After fully soaking for 10-12 hours, filter to obtain a saturated hydrogel, dry it at 50-60°C for 2 days, add 5-10g of graphene powder after drying, mix and crush to prepare a nano-composite early strength and viscosity-enhancing material.

3. The elasticity reducing agent for early-strength anti-seepage shotcrete in water-rich areas according to claim 2, characterized in that: The modulus of the sodium silicate is 2.2-2.6; the mass concentration of calcium nitrate in the mixed solution of calcium nitrate and aluminum nitrate is 10-15%, and the mass concentration of aluminum nitrate is 20-30%; PCE is a polycarboxylate water reducer, and the mass concentration is 5-10%.

4. The elasticity reducing agent for early-strength anti-seepage shotcrete in water-rich areas according to claim 2, characterized in that: The molecular weight of the cationic polyacrylamide is 600,000 to 1,000,000.

5. The elasticity reducing agent for early-strength anti-seepage shotcrete in water-rich areas according to claim 2, characterized in that: The graphene is industrial-grade graphene with a density of 10 to 50 g / cm3.

6. The elasticity reducing agent for early-strength and anti-seepage shotcrete in water-rich areas according to claim 1, characterized in that: The filling material is composed of one or more of stone powder, silica ash and tailings powder.

7. The method for preparing the elasticity reducing agent for early strength and anti-seepage shotcrete in water-rich areas according to any one of claims 1 to 6, characterized in that: The early strength component, the accelerating component, the regulating component and the filling material are mixed according to the designed mass ratio to obtain the elasticity reducing agent for the early strength and anti-seepage shotcrete in the water-rich area.

8. The method for preparing the elasticity reducing agent for early strength and anti-seepage shotcrete in water-rich areas according to claim 7, characterized in that: The nano-composite early-strengthening and thickening material is prepared by modifying cationic polyacrylamide with hydrogel and then adsorbing CASH nano-crystal core as a thickening and early-strengthening component.

9. The use of the elasticity reducing agent for early strength and anti-seepage shotcrete in water-rich areas according to any one of claims 1 to 6, characterized in that: The elasticity reducing agent is added to the shotcrete by internal mixing, that is, replacing cement. The amount of the elasticity reducing agent is 1-3% of the mass of the cementitious material in the shotcrete.

Citation Information

Patent Citations

  • Graphene concrete surface reinforcing agent and using method thereof

    CN108840595A

  • Coagulating early strength agent, preparation method thereof and concrete composition

    CN115893895A

  • High-performance sprayed concrete for subsea tunnel and construction application method of high-performance sprayed concrete

    CN117776639A

  • Elasticity reducing agent for low-carbon high-compactness sprayed concrete as well as preparation method and application of elasticity reducing agent

    CN119241127A